Preparation method of corrosion-resistant Ti-Ru alloy plate
By optimizing the fabric method and forging process, combined with multi-pass rolling and heat treatment, the problems of uneven distribution of Ru elements and poor mechanical properties in Ti-Ru alloy are solved, and uniform structure and excellent corrosion resistance of alloy sheets are achieved. Mechanical properties.
Patent Information
- Application Number
- CN202411648868.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-19
AI Technical Summary
During the processing of existing Ti-Ru alloys, there are problems of uneven distribution of Ru elements and poor mechanical properties, which limits its wide application in chemical equipment and reaction vessels.
By optimizing the fabric method, avoiding segregation of Ru elements, and using multi-fire forging above the phase change point combined with commutation upsetting technology, an alloy slab with uniform structure is obtained. Then, through multi-pass rolling and heat treatment, the structural structure of the alloy sheet is adjusted to achieve excellent corrosion resistance and mechanical properties.
The uniform distribution of Ru elements is achieved, smelting defects are avoided, the mechanical properties of Ti-Ru alloy sheets are significantly improved, and its excellent corrosion resistance is ensured.
Smart Images

Figure CN119426401A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloys, and in particular to a method for preparing a corrosion-resistant Ti-Ru alloy plate. Background Art
[0002] Industrial pure titanium has excellent corrosion resistance and high specific strength. It is widely used in seawater cooling and desalination, as well as in salt solution, wet chlorine and nitric acid solution transportation equipment. The corrosion resistance of titanium comes from the dense oxide film formed when it is oxidized, which can hinder the dissolution of the matrix in the corrosive medium and increase the self-corrosion potential. However, pure titanium will be severely corroded in reducing acids and prone to crevice corrosion in high-temperature chloride solutions, which limits its wider application. Studies have shown that adding trace amounts of Ru elements to pure titanium will form dispersed Ru-rich precipitates on the α-phase matrix. The Ru-rich surfaces produced during the dissolution of these precipitates accelerate the reduction of hydrogen ions, thereby shifting the corrosion potential of the alloy to the positive direction and inhibiting further corrosion of the alloy matrix, thereby effectively improving the corrosion resistance of titanium alloys.
[0003] At present, there are two problems in the processing of Ti-Ru alloy: the first is the uniformity of Ru element distribution. The Ru content in Ti-Ru alloy is usually around 0.1%, and its melting point (2310℃) and density (12.3g / cm 3 ) are greater than the matrix element Ti, so segregation and inclusion defects are prone to occur during smelting. Patent CN101481759A discloses a method for preparing a Ru-containing titanium alloy, which directly mixes Ru powder, intermediate alloy and sponge titanium, and presses electrodes. Since the particle size of Ru powder is very small, the adhesion with large particles of sponge titanium and intermediate alloy is poor. Therefore, direct mixing is very likely to cause Ru powder to concentrate at the bottom and cause certain losses. This can be seen from the inconsistent composition of Ru elements at the head and tail of the ingot in its implementation case, and the measured composition is less than the nominal composition (the maximum deviation reaches 9%). Secondly, corrosion-resistant Ti-Ru alloys usually need to be processed into plates for application in various chemical equipment, reaction vessels and pipelines, etc. Its application scenarios not only require excellent corrosion resistance, but also have certain requirements for mechanical properties. Therefore, how to optimize the grain size, texture characteristics and phase composition of Ti-Ru alloy plates by setting reasonable forging, rolling and heat treatment processes so that the final alloy plates have both good corrosion resistance and mechanical properties is a key problem to be solved. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a corrosion-resistant Ti-Ru alloy plate in view of the shortcomings of the above-mentioned prior art. The method avoids the segregation of Ru elements and reduces losses by optimizing the material distribution method, obtains an alloy slab with uniform structure by multiple forgings above the phase transformation point combined with a reversing upsetting process, and obtains a composite structure consisting of a fine-grained matrix and a nano-precipitated phase by controlling the insulation temperature of multiple rolling passes and the deformation amount of single rolling passes and the heat treatment system, so that the Ti-Ru alloy plate has both excellent corrosion resistance and mechanical properties, solving the problem that the Ti-Ru alloy is prone to smelting defects and poor mechanical properties in the prior art.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a corrosion-resistant Ti-Ru alloy plate, characterized in that the method comprises the following steps:
[0006] Step 1, using titanium sponge and Ru powder as raw materials, and preparing the materials according to the designed composition of the target product; the titanium sponge includes titanium sponge with a particle size of 9.8 mm to 23.4 mm and a particle size not exceeding 5 mm, and the particle size of the Ru powder does not exceed 50 μm; the designed composition of the target product is calculated by mass content: Ru 0.08% to 0.1%, and the rest is Ti;
[0007] Step 2: Partially mix, layer and press the raw materials prepared in step 1, and then perform vacuum consumable smelting three times to obtain an alloy ingot;
[0008] Step 3, subjecting the alloy ingot obtained in step 2 to single-fire forging in a high-temperature single-phase region to obtain a single-fire forged ingot;
[0009] Step 4: subjecting the one-fire forging ingot obtained in step 3 to two-fire forging and three-fire forging in a high-temperature single-phase region to obtain a three-fire forging ingot;
[0010] Step 5, subjecting the three-fire forging ingot obtained in step 4 to four-fire slab forging in the two-phase region to obtain an alloy slab;
[0011] Step 6: grinding and repairing the surface of the alloy slab obtained in step 5, and then performing multiple-pass rolling on a reversible hot rolling mill to obtain an alloy plate;
[0012] Step 7: straighten and heat treat the alloy plate obtained in step 6 to obtain a corrosion-resistant Ti-Ru alloy plate.
[0013] The above-mentioned method for preparing a corrosion-resistant Ti-Ru alloy sheet is characterized in that the process of partial mixing in step 2 is: all Ru powders and sponge titanium with a particle size not exceeding 5 mm are uniformly mixed to obtain an alloy mixture, and the mass ratio of Ru powder to sponge titanium in the alloy mixture is 1:20 to 1:50. The mixing process is the process of diffusion and adsorption of Ru powder in sponge titanium. Due to the limited adsorption capacity of sponge titanium, by controlling the ratio of the two, it is avoided that the sponge titanium content is too little to fully adsorb Ru powder, causing the remaining Ru powder to precipitate at the bottom, and at the same time, it is avoided that the sponge titanium content is too much so that the diffusion of Ru powder is blocked, resulting in its uneven distribution.
[0014] The above-mentioned method for preparing a corrosion-resistant Ti-Ru alloy plate is characterized in that the process of layered laying in step 2 is: first lay a layer of titanium sponge with a particle size of 9.8mm to 23.4mm as the bottom layer, then lay a layer of alloy mixture as the middle layer on the bottom layer, and then lay a layer of titanium sponge with a particle size of 9.8mm to 23.4mm on the middle layer as the top layer, and lay the materials in layers alternately according to the rule of titanium sponge-alloy mixture-titanium sponge; the number of times of layered alternating laying is 3 to 5 layers. Generally, the actual mass content of the Ru element in the alloy ingot deviates from the nominal mass content by no more than 5%.
[0015] The above-mentioned method for preparing a corrosion-resistant Ti-Ru alloy plate is characterized in that the temperature of the first-fire forging in step three is 200°C to 250°C higher than the phase transformation point, and the deformation of the first-fire forging is not less than 40%.
[0016] The above-mentioned method for preparing a corrosion-resistant Ti-Ru alloy plate is characterized in that the temperature of the second-fire forging in step four is 100°C to 150°C higher than the phase transformation point, and the deformation of the second-fire forging is not less than 30%; the temperature of the third-fire forging is 20°C to 50°C higher than the phase transformation point, and the deformation of the third-fire forging is not less than 30%.
[0017] The above-mentioned method for preparing a corrosion-resistant Ti-Ru alloy plate is characterized in that the two-fire forging and three-fire forging in step four are reversing three-upsetting and three-drawing, that is, the ingot is rotated 90° after being forged and deformed in one direction, and then rotated 90° again after being deformed in a new direction, and returns to the original direction after rotating and deforming three times.
[0018] The above-mentioned method for preparing a corrosion-resistant Ti-Ru alloy plate is characterized in that the temperature of the four-fire slab forging in step five is 10°C to 50°C lower than the phase transformation point, and the deformation of the four-fire slab forging is not less than 60%.
[0019] The above-mentioned method for preparing a corrosion-resistant Ti-Ru alloy plate is characterized in that the insulation temperature of the multiple rolling passes in step six is 20°C to 50°C lower than the phase transformation point, and the deformation amount of a single rolling pass is 15% to 50%.
[0020] The above-mentioned method for preparing a corrosion-resistant Ti-Ru alloy plate is characterized in that the heat treatment temperature in step seven is 600°C to 700°C, the heat treatment time is 30min to 60min, and the cooling method is air cooling.
[0021] The above-mentioned method for preparing a corrosion-resistant Ti-Ru alloy plate is characterized in that the room temperature tensile strength of the corrosion-resistant Ti-Ru alloy plate in step seven is above 490 MPa and the elongation is above 23%.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] 1. The present invention forms an alloy mixture by mixing Ru powder with sponge titanium with a smaller particle size, and then distributes the alloy mixture in layers so that the alloy mixture is dispersed and wrapped in sponge titanium with a larger particle size, and then presses and melts to obtain an alloy ingot, thereby improving the distribution uniformity of Ru powder, effectively avoiding metallurgical defects such as segregation and inclusion of high-melting-point, high-density Ru elements, laying the foundation for subsequent hot processing, and reducing the loss of Ru powder in the process of batching and electrode pressing, thereby reducing the smelting cost.
[0024] 2. The present invention adopts multi-fire forging above the phase transformation point combined with a reversing upsetting process to avoid the occurrence of deformation dead zones during the forging process and obtain an alloy slab with uniform structure. Then, by controlling the multi-fire forging temperature and deformation amount, the alloy slab structure is made more uniform and fine, avoiding defects such as cracking, curling and thickness deviation that are prone to occur during subsequent plate processing.
[0025] 3. The present invention controls the holding temperature of multiple rolling passes and the deformation amount of single rolling pass, and combines the heat treatment system to effectively regulate the Ti-Ru alloy plate to obtain a composite structure consisting of a refined α-grain matrix and a nano-scale Ru-rich precipitate phase. On the basis of ensuring that the Ti-Ru alloy plate has excellent corrosion resistance, its mechanical properties are significantly improved, and the room temperature tensile strength of the Ti-Ru alloy plate is above 490MPa, and the elongation is above 23%.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the microstructure diagram of the corrosion-resistant Ti-0.08Ru alloy plate prepared in Example 1 of the present invention.
[0028] Figure 2 This is the morphology of Ru-rich nano-precipitates in the corrosion-resistant Ti-0.08Ru alloy plate prepared in Example 1 of the present invention.
[0029] Figure 3 This is the microstructure diagram of the corrosion-resistant Ti-0.086Ru alloy plate prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0030] Example 1
[0031] This embodiment includes the following steps:
[0032] Step 1, using grade 0 titanium sponge and Ru powder with a mass purity of 99.90% as raw materials, and preparing raw materials with a total weight of 25 kg according to the designed composition of the target product Ti-0.08Ru; the grade 0 titanium sponge includes grade 0 titanium sponge with a particle size of 9.8mm-23.4mm and a particle size not exceeding 5mm, and the particle size of the Ru powder does not exceed 50μm; the designed composition of the target product Ti-0.08Ru is calculated by mass content: Ru 0.08%, and the rest is Ti;
[0033] Step 2: Partially mix, layer and press the raw materials prepared in step 1, and then perform vacuum consumable smelting three times to obtain an alloy ingot; the process of partial mixing is: all Ru powder and grade 0 sponge titanium with a particle size not exceeding 5 mm are mixed evenly to obtain an alloy mixture, and the mass ratio of Ru powder to grade 0 sponge titanium in the alloy mixture is 1:20; the process of layered distribution is: first lay a layer of sponge titanium with a particle size of 9.8 mm to 23.4 mm as a bottom layer, then lay a layer of alloy mixture on the bottom layer as an intermediate layer, and then lay a layer of sponge titanium with a particle size of 9.8 mm to 23.4 mm on the intermediate layer as a top layer, and layer and alternately distribute the materials according to the rule of sponge titanium-alloy mixture-sponge titanium, and the number of layered and alternate distribution is 3 layers;
[0034] Step 3, subjecting the alloy ingot obtained in step 2 to single-fire forging in a high-temperature single-phase region to obtain a single-fire forged ingot; the temperature of the single-fire forging is 250° C. higher than the phase transition point, the holding time is 100 minutes, and the deformation of the single-fire forging is 43%;
[0035] Step 4, the single-fire forging ingot obtained in step 3 is subjected to double-fire forging and triple-fire forging in a high-temperature single-phase region to obtain a triple-fire forging ingot; the temperature of the double-fire forging is 150°C higher than the phase transition point, the holding time is 90 minutes, and the deformation of the double-fire forging is 43%; the temperature of the triple-fire forging is 20°C higher than the phase transition point, the holding time is 90 minutes, and the deformation of the triple-fire forging is 35%; the double-fire forging and triple-fire forging are reversing three-upsetting and three-drawing, that is, the ingot is rotated 90° after forging and deformation in one direction, and rotated 90° again after deformation in the new direction, and returns to the original direction after rotation and deformation three times;
[0036] Step 5, subjecting the three-fire forging ingot obtained in step 4 to four-fire slab forging in the two-phase region to obtain an alloy slab; the temperature of the four-fire slab forging is 50° C. lower than the phase transition point, the holding time is 80 minutes, and the deformation of the four-fire slab forging is 66%;
[0037] Step 6: grinding and repairing the surface of the alloy slab obtained in step 5, and then performing multiple-pass rolling on a reversible hot rolling mill to obtain an alloy plate; the insulation temperature of the multiple-pass rolling is 20° C. lower than the phase transition point, the insulation time is 40 minutes, and the deformation of a single-pass rolling is 15% to 30%;
[0038] Step 7: straighten and heat treat the alloy plate obtained in step 6 to obtain a corrosion-resistant Ti-0.08Ru alloy plate; the heat treatment temperature is 670°C, the heat treatment time is 60 minutes, and the cooling method is air cooling; the room temperature tensile strength of the corrosion-resistant Ti-0.08Ru alloy plate is 497MPa, and the elongation is 29%.
[0039] Figure 1 The microstructure of the corrosion-resistant Ti-0.08Ru alloy plate prepared in this embodiment is shown in FIG. Figure 2 The Ru-rich nano-precipitate phase morphology in the corrosion-resistant Ti-0.08Ru alloy plate prepared in this embodiment is combined with Figure 1 and Figure 2 It can be seen that the α grain size in the Ti-0.08Ru alloy plate is about 10 μm, and a large number of uniform nanoscale Ru-rich precipitates are precipitated inside it, which is a typical organizational structure with excellent corrosion resistance.
[0040] Example 2
[0041] This embodiment includes the following steps:
[0042] Step 1, using grade 0 titanium sponge and Ru powder with a purity of 99.90% by mass as raw materials, and preparing raw materials with a total weight of 22 kg according to the designed composition of the target product Ti-0.086Ru; the grade 0 titanium sponge includes grade 0 titanium sponge with a particle size of 9.8 mm to 23.4 mm and a particle size not exceeding 5 mm, and the particle size of the Ru powder does not exceed 50 μm; the designed composition of the target product Ti-0.086Ru is calculated by mass content: Ru 0.086%, and the rest is Ti;
[0043] Step 2: Partially mix, layer and press the raw materials prepared in step 1, and then perform vacuum consumable smelting three times to obtain an alloy ingot; the process of partial mixing is: all Ru powder and grade 0 sponge titanium with a particle size not exceeding 5 mm are mixed evenly to obtain an alloy mixture, and the mass ratio of Ru powder to grade 0 sponge titanium in the alloy mixture is 1:50; the process of layered distribution is: first lay a layer of sponge titanium with a particle size of 9.8 mm to 23.4 mm as a bottom layer, then lay a layer of alloy mixture on the bottom layer as an intermediate layer, and then lay a layer of sponge titanium with a particle size of 9.8 mm to 23.4 mm on the intermediate layer as a top layer, and layer and alternately distribute the materials according to the rule of sponge titanium-alloy mixture-sponge titanium, and the number of layered and alternate distribution is 4 layers;
[0044] Step 3: subjecting the alloy ingot obtained in step 2 to single-fire forging in a high-temperature single-phase region to obtain a single-fire forged ingot; the temperature of the single-fire forging is 200° C. higher than the phase transition point, the holding time is 100 min, and the deformation of the single-fire forging is 41%;
[0045] Step 4, the single-fire forging ingot obtained in step 3 is subjected to double-fire forging and triple-fire forging in a high-temperature single-phase region to obtain a triple-fire forging ingot; the temperature of the double-fire forging is 100°C higher than the phase transition point, the holding time is 90 minutes, and the deformation of the double-fire forging is 36%; the temperature of the triple-fire forging is 30°C higher than the phase transition point, the holding time is 90 minutes, and the deformation of the triple-fire forging is 38%; the double-fire forging and triple-fire forging are reversing three-upsetting and three-drawing, that is, the ingot is rotated 90° after forging and deformation in one direction, and rotated 90° again after deformation in the new direction, and returns to the original direction after rotation and deformation three times;
[0046] Step 5, subjecting the three-fire forging ingot obtained in step 4 to four-fire slab forging in the two-phase region to obtain an alloy slab; the temperature of the four-fire slab forging is 30° C. lower than the phase transition point, the holding time is 85 min, and the deformation of the four-fire slab forging is 70%;
[0047] Step 6: grinding and repairing the surface of the alloy slab obtained in step 5, and then performing multiple-pass rolling on a reversible hot rolling mill to obtain an alloy plate; the holding temperature of the multiple-pass rolling is 35° C. lower than the phase transition point, the holding time is 45 minutes, and the deformation of a single-pass rolling is 20% to 40%;
[0048] Step 7: straighten and heat treat the alloy plate obtained in step 6 to obtain a corrosion-resistant Ti-0.086Ru alloy plate; the heat treatment temperature is 700°C, the heat treatment time is 45 minutes, and the cooling method is air cooling; the room temperature tensile strength of the corrosion-resistant Ti-0.086Ru alloy plate is 492MPa, and the elongation is 29%.
[0049] Figure 3 The microstructure of the corrosion-resistant Ti-0.086Ru alloy plate prepared in this embodiment is as follows: Figure 3 It can be seen that the α matrix grains in the corrosion-resistant Ti-0.086Ru alloy plate are small and uniform in size.
[0050] Example 3
[0051] This embodiment includes the following steps:
[0052] Step 1, using grade 0 titanium sponge and Ru powder with a mass purity of 99.90% as raw materials, and preparing raw materials with a total weight of 26 kg according to the designed composition of the target product Ti-0.10Ru; the grade 0 titanium sponge includes grade 0 titanium sponge with a particle size of 9.8mm-23.4mm and a particle size not exceeding 5mm, and the particle size of the Ru powder does not exceed 50μm; the designed composition of the Ti-0.10Ru of the target product is calculated by mass content: Ru 0.10%, and the rest is Ti;
[0053] Step 2: Partially mix, layer and press the raw materials prepared in step 1, and then perform vacuum consumable smelting three times to obtain an alloy ingot; the process of partial mixing is: all Ru powder and grade 0 sponge titanium with a particle size not exceeding 5 mm are mixed evenly to obtain an alloy mixture, and the mass ratio of Ru powder to grade 0 sponge titanium in the alloy mixture is 1:25; the process of layered distribution is: first lay a layer of sponge titanium with a particle size of 9.8 mm to 23.4 mm as a bottom layer, then lay a layer of alloy mixture on the bottom layer as an intermediate layer, and then lay a layer of sponge titanium with a particle size of 9.8 mm to 23.4 mm on the intermediate layer as a top layer, and layer and alternately distribute the materials according to the law of sponge titanium-alloy mixture-sponge titanium, and the number of layered and alternate distribution is 3 layers;
[0054] Step 3, subjecting the alloy ingot obtained in step 2 to single-fire forging in a high-temperature single-phase region to obtain a single-fire forged ingot; the temperature of the single-fire forging is higher than the phase transition point of 215° C., the holding time is 100 minutes, and the deformation of the single-fire forging is 45%;
[0055] Step 4, the single-fire forging ingot obtained in step 3 is subjected to double-fire forging and triple-fire forging in a high-temperature single-phase region to obtain a triple-fire forging ingot; the temperature of the double-fire forging is 115°C higher than the phase transition point, the holding time is 90 minutes, and the deformation of the double-fire forging is 32%; the temperature of the triple-fire forging is 50°C higher than the phase transition point, the holding time is 90 minutes, and the deformation of the triple-fire forging is 36%; the double-fire forging and triple-fire forging are reversing three-upsetting and three-drawing, that is, the ingot is rotated 90° after forging and deformation in one direction, and rotated 90° again after deformation in the new direction, and returns to the original direction after rotation and deformation three times;
[0056] Step 5, the three-fire forging ingot obtained in step 4 is subjected to four-fire slab forging in the two-phase region to obtain an alloy slab; the temperature of the four-fire slab forging is 10° C. lower than the phase transition point, the holding time is 85 min, and the deformation of the four-fire slab forging is 63%;
[0057] Step 6: grinding and repairing the surface of the alloy slab obtained in step 5, and then performing multiple-pass rolling on a reversible hot rolling mill to obtain an alloy plate; the insulation temperature of the multiple-pass rolling is 50° C. lower than the phase transition point, the insulation time is 45 minutes, and the deformation of a single-pass rolling is 25% to 50%;
[0058] Step seven, straighten and heat treat the alloy plate obtained in step six to obtain a corrosion-resistant Ti-0.10Ru alloy plate; the heat treatment temperature is 600°C, the heat treatment time is 30 minutes, and the cooling method is air cooling; the room temperature tensile strength of the corrosion-resistant Ti-0.10Ru alloy plate is 510MPa, and the elongation is 23%.
[0059] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a corrosion-resistant Ti-Ru alloy sheet, characterized in that: The method comprises the following steps: Step 1, using titanium sponge and Ru powder as raw materials, and preparing the materials according to the designed composition of the target product; the titanium sponge includes titanium sponge with a particle size of 9.8 mm to 23.4 mm and a particle size not exceeding 5 mm, and the particle size of the Ru powder does not exceed 50 μm; the designed composition of the target product is calculated by mass content: Ru 0.08% to 0.1%, and the rest is Ti; Step 2: Partially mix, layer and press the raw materials prepared in step 1, and then perform vacuum consumable smelting three times to obtain an alloy ingot; Step 3, subjecting the alloy ingot obtained in step 2 to single-fire forging in a high-temperature single-phase region to obtain a single-fire forged ingot; Step 4: subjecting the one-fire forging ingot obtained in step 3 to two-fire forging and three-fire forging in a high-temperature single-phase region to obtain a three-fire forging ingot; Step 5, subjecting the three-fire forging ingot obtained in step 4 to four-fire slab forging in the two-phase region to obtain an alloy slab; Step 6: grinding and repairing the surface of the alloy slab obtained in step 5, and then performing multiple-pass rolling on a reversible hot rolling mill to obtain an alloy plate; Step 7: straighten and heat treat the alloy plate obtained in step 6 to obtain a corrosion-resistant Ti-Ru alloy plate.
2. The method for preparing a corrosion-resistant Ti-Ru alloy sheet according to claim 1, characterized in that: The process of partial mixing in step 2 is: all the Ru powder and sponge titanium with a particle size not exceeding 5 mm are uniformly mixed to obtain an alloy mixture, and the mass ratio of Ru powder to sponge titanium in the alloy mixture is 1:20 to 1:
50.
3. The method for preparing a corrosion-resistant Ti-Ru alloy sheet according to claim 2, characterized in that: The process of layered laying in step 2 is: first lay a layer of sponge titanium with a particle size of 9.8mm to 23.4mm as the bottom layer, then lay a layer of alloy mixture on the bottom layer as the middle layer, and then lay a layer of sponge titanium with a particle size of 9.8mm to 23.4mm on the middle layer as the top layer, and lay the materials in layers alternately according to the rule of sponge titanium-alloy mixture-sponge titanium; the number of layered alternating laying is 3 to 5 layers.
4. The method for preparing a corrosion-resistant Ti-Ru alloy sheet according to claim 1, characterized in that: The temperature of the first-fire forging in step 3 is 200° C. to 250° C. higher than the phase transformation point, and the deformation of the first-fire forging is not less than 40%.
5. The method for preparing a corrosion-resistant Ti-Ru alloy sheet according to claim 1, characterized in that: The temperature of the second-fire forging in step 4 is 100°C to 150°C higher than the phase transformation point, and the deformation of the second-fire forging is not less than 30%; the temperature of the third-fire forging is 20°C to 50°C higher than the phase transformation point, and the deformation of the third-fire forging is not less than 30%.
6. The method for preparing a corrosion-resistant Ti-Ru alloy sheet according to claim 1, characterized in that: The two-fire forging and three-fire forging in step 4 are three-upsetting and three-drawing with reversing directions, that is, the ingot is rotated 90° after forging and deformation in one direction, and then rotated 90° again after deformation in the new direction, and returns to the original direction after rotation and deformation three times.
7. The method for preparing a corrosion-resistant Ti-Ru alloy sheet according to claim 1, characterized in that: The temperature of the four-fire slab forging in step 5 is 10° C. to 50° C. lower than the phase transformation point, and the deformation of the four-fire slab forging is not less than 60%.
8. The method for preparing a corrosion-resistant Ti-Ru alloy sheet according to claim 1, characterized in that: The holding temperature of the multi-pass rolling in step 6 is 20° C. to 50° C. lower than the phase transformation point, and the deformation amount of a single-pass rolling is 15% to 50%.
9. The method for preparing a corrosion-resistant Ti-Ru alloy sheet according to claim 1, characterized in that: The heat treatment temperature in step seven is 600° C. to 700° C., the heat treatment time is 30 min to 60 min, and the cooling method is air cooling.
10. The method for preparing a corrosion-resistant Ti-Ru alloy sheet according to claim 1, characterized in that: The room temperature tensile strength of the corrosion-resistant Ti-Ru alloy plate in step seven is above 490 MPa, and the elongation is above 23%.
Citation Information
Patent Citations
Method for preparing ruthenium-containing corrosion resistant titanium alloy
CN101481759A
Low-cost medium-high-strength corrosion-resistant titanium alloy and processing method thereof
CN104152744A
Element-dropped Si-Cr-M solid solution powder and preparation method thereof
CN105855536A
Process for producing ru-containing corrosion-resistant titanium alloy
CN106661669A
Preparation method of moderate-strength and high-toughness titanium alloy oversized ring material
CN109439936A